A Review on medicinal plants with Anticancer activity - Dhanalakshmi., M (International Journal of Pharmaceutical & Biological Archive, 2018)
Cancer is a major public health burden in both developed and developing countries. Cancer after cardiovascular disease is the second leading cause of death. Cancer is the abnormal growth of cells in our bodies that can lead to death. India is a peninsula of herbal hub, in which Ayurvedics system of medicine has flourished as an enlightment in the field of Medicine. Currently medicinal plants have become the paramount source of drug discovery in research for treating diverse form of diseases including Cancer. With the current decline in the number of new molecular entities from the Pharmaceutical industry, novel anticancer agents are being sought from traditional medicines. This article reveals a detailed review of ethno medicinally important plants in cancer from medicinal plants which will be useful to treat various types of cancer.